FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU NONSUICIDAL SELF-INJURY (NSSI) PADA REMAJA PUTRI - Zalyaleolita Yuliandhani Helmi Zakaria, (2020)
Nonsuicidal Self-Injury (NSSI) is an intentional self-injuring behavior without the intention of suicide. NSSI acts as a cause of suicide attempts in teenage girls in various places in the world. This study aims to determine the characteristics, background, and factors that influence NSSI behavior in teenage girls. This research uses analytic descriptive with qualitative approach. The sampling technique uses purposive sampling. The subjects of this study were 2 teenage girls with a history of NSSI behavior. Data collection techniques used in this study were semitructured interviews, observations, and questionnaires. The credibility test in this study uses technical triangulation and member check. The results showed that the factors causing NSSI behavior were emotional dysregulation which led to the selection of NSSI behavior as a maladaptive coping mechanism, due to problems such as negative peer influence through bullying and disharmony relationships within the family. NSSI behavioral methods that are often used are self-cutting and selfhitting. NSSI behavior can also arise due to the lack of positive alternatives to overcome problems experienced by someone with NSSI tendencies